Bun Cheese Sausage: Protein Source Snack Made From Mackerel And Bogor Taro Flour Substitution - Ani Nuraeni; Aqilla Faiza Hidayat; Shabrina Dhiya Qurraru Aini; Qonitah Hafshah; Annisa Rizkiriani; Vieta Annisa Nurhidayati (Media Publikasi Cendekia Indonesia, 2026)
Teenagers, especially school children, are very vulnerable to various nutritional problems caused by unhealthy diets. Moreover, eating patterns in teenagers are very easily influenced by the surrounding environment. As we know, it is currently easy to find snacks that are high in sodium, high in sugar, and high in saturated fat, which can have bad consequences for the health of children and teenagers in the future. For this reason, it is necessary to develop nutritious food products that favor local food ingredients. Mackerel provides essential nutrients and is a source of high protein with lower saturated fat content compared to other animal protein sources. This research aims to develop sausage from mackerel with talas flour as an added value of local food. Mackerel sausage with taro flour is made by mixing mackerel with various ingredients such as taro flour, tapioca flour, egg white, garlic, then steamed until cooked. The results showed that mackerel sausage has a soft texture and savory taste that is liked by various groups, especially children and teenagers. Processing mackerel into sausage can also increase the consumption of this food and encourage a healthy diet. Mackerel sausage is one of the food product developments that should be further developed to support a healthy diet, especially in children and teenagers.